Pre-Pregnancy Intimate Partner Violence and Short Interbirth Interval: The Role of Insurance Status - Rozario, Sylvia S. (Journal of interpersonal violence, 2021)
Short interbirth interval (IBI) has serious adverse health consequences, yet has an estimated prevalence of 35% in the United States. Similarly, intimate partner violence (IPV) around time of pregnancy, experienced by approximately 5% of women, is associated with increased risk of poor pregnancy outcomes. IPV might compromise women’s decision-making, contributing to unintended pregnancy and short IBI. This study examines the relationship between pre-pregnancy IPV and short IBI, and whether insurance status moderates this relationship among multiparous women who responded to the 2009–2011 Pregnancy Risk Assessment Monitoring System survey (N = 13,675). Pre-pregnancy IPV (yes; no), insurance status (Private insurance; Medicaid/public insurance; no insurance), and short IBI (yes; no) were examined. Insurance status was identified as an effect modifier (p = .03), and maternal age, maternal and paternal education, marital status, and drinking alcohol were identified as potential confounders. Multiple logistic regression analysis stratified by insurance status provided adjusted odds ratios (aOR) with corresponding 95% confidence intervals (CI). Overall, 4.6% of women reported IPV before pregnancy, and 48% had a short IBI. When stratified by insurance status, the odds of short IBI was about 3 times higher among women with no insurance and women on Medicaid/public insurance who reported IPV compared to women who did not report IPV (aOR = 3.36, 95% CI = [1.02, 8.02], and aOR = 2.50, 95% CI = [1.04, 5.92], respectively). There was no observed significant difference in the likelihood of short IBI by experience of IPV among privately insured women. Findings from this study strengthen the evidence that women who experience IPV before pregnancy are significantly more likely to have short IBI compared to women who do not experience pre-pregnancy IPV. Furthermore, the odds of short IBI is highest among women experiencing pre-pregnancy IPV who are uninsured or on Medicaid/public insurance.